2020
DOI: 10.1155/2020/8846544
|View full text |Cite
|
Sign up to set email alerts
|

Social Symptoms of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is typically well recognized by its characteristic motor symptoms (e.g., bradykinesia, rigidity, and tremor). The cognitive symptoms of PD are increasingly being acknowledged by clinicians and researchers alike. However, PD also involves a host of emotional and communicative changes which can cause major disruptions to social functioning. These incude problems producing emotional facial expressions (i.e., facial masking) and emotional speech (i.e., dysarthria), as well as difficulties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 130 publications
2
35
0
Order By: Relevance
“…Our findings suggest that the cognitive flexibility of executive function and visuospatial ability are the susceptible cognitive domains in female patients with PD and have a higher risk of being damaged, which may result from the loss of estrogen protection. Moreover, growing evidence has also shown the development of a host of socioaffective troubles in addition to neurocognitive dysfunctions in the disease course of PD [39]. Our previous study also found susceptibility to social cognition in female patients with PD [40].…”
Section: Discussionsupporting
confidence: 68%
“…Our findings suggest that the cognitive flexibility of executive function and visuospatial ability are the susceptible cognitive domains in female patients with PD and have a higher risk of being damaged, which may result from the loss of estrogen protection. Moreover, growing evidence has also shown the development of a host of socioaffective troubles in addition to neurocognitive dysfunctions in the disease course of PD [39]. Our previous study also found susceptibility to social cognition in female patients with PD [40].…”
Section: Discussionsupporting
confidence: 68%
“…She had characteristic Parkinsonian gait. She was not able to express non-verbally through facial expressions due to masked face 5 . She was in stage 3 of Hoehn and Yahr scale for classification of PD which suggested bilateral involvement with postural instability but independent…”
Section: Personmentioning
confidence: 99%
“…Social perception is one of the main social abilities affected in patients with PD ( Buxton et al, 2013 ), particularly for what concerns action observation ( Agosta et al, 2017 ), face perception ( Cardoso et al, 2010 ), and emotion recognition ( Argaud et al, 2018 ). These social anomalies may lead to a wide range of negative outcomes, such as loneliness, stigma, and dehumanization, which might impair the patient’s life more than other symptoms ( Prenger et al, 2020 ). Despite this evidence, the neural substrates of social perception deficits in PD remain to be clarified ( Bell et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%